Logopedyczne badania dzieci i młodzieży z zaburzeniami mowy i języka uwarunkowanymi korowo. Projekt badań własnych - Kurowska, Marlena (Teoria i praktyka logopedyczna. Wybrane zagadnienia, 2018)
The speech and language disorders of children caused by trauma and/or malfunction of CNS are currenttly an important issue in the Polish logopedic. The disorders can have developmental or acquired form. The most researches report about developmental disorders. Speech and language therapy practice shows that symptomps are of aphasic character, such as difficulty in updating the correct word, paraphasias. In the paper I would like to present my own research project. The main objective is the comparison of the level of language competence of children and youth with structural or functional changes in the brain. The key issue is the time of occurrence of a pathogenic agent: before and during language acquisition or after the patients learn the basics of language. The project is also about linguistic and non-linguistic behavior conditioned by the changes and their location in the brain.